The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-35982012000900016
|View full text |Cite
|
Sign up to set email alerts
|

Technological quality of eggs in relation to the age of laying hens and Japanese quails

Abstract: -This investigation was carried out to evaluate certain egg quality characteristics of ISA Brown laying hens and Japanese quails (Coturnix coturnix japonica) in relation to their age. One hundred forty-four brown-egg ISA Brown laying hens and one hundred female quails were used in the study. A total of 1,678 eggs of laying hens and 2,060 eggs of Japanese quails were used during the experiment. The eggs for technological values were collected during two consecutive days in a 4-week period when the laying hens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 9 publications
9
11
1
3
Order By: Relevance
“…The highest average SI was observed in group GG (78.31±0.53%), vs the lowest in WG quails (77.55±0.62%). Our data about shape index agreed with those of other researchers having assessed quail egg quality (8,(11)(12)(13)(14)(15). From the surface inward, the egg consists of a shell with membranes, albumen and yolk.…”
Section: Methodssupporting
confidence: 90%
“…The highest average SI was observed in group GG (78.31±0.53%), vs the lowest in WG quails (77.55±0.62%). Our data about shape index agreed with those of other researchers having assessed quail egg quality (8,(11)(12)(13)(14)(15). From the surface inward, the egg consists of a shell with membranes, albumen and yolk.…”
Section: Methodssupporting
confidence: 90%
“…The tendency was also mentioned by other researchers on quail egg quality (13)(14)(15)(16). Like us, Yilmaz-Dikmen and Ipek (17), Vali et al (18) and Zita et al (19) found out lower egg weight by the end of the production cycle. The highest mean egg weight for the period was registered in WG eggs (14.04±0.32 g), followed by GG (13.65±0.27 g) and GL (12.79±0.29 g) eggs.…”
Section: Resultsmentioning
confidence: 55%
“…Shell quality including thickness and strength were known to decrease with age of hens, probably due to poorer functioning on calcium metabolism (Zita et al, 2012). Bone (Moreki et al, 2011) and serum calcium (Garlich et al, 1984) status that represent calcium metabolism were also diminished with increasing age.…”
Section: Discussionmentioning
confidence: 99%